(untitled) (Proceedings of Southern Federal University. Philology, 2014)
Key words: ancient world, metamorphosis, myth, mythologeme, syncretism, ritual, syncretism. The article considers the notion of inspiration - a peculiar state which has been inseparably linked to creativity since the ancient world. The mythological invariants of the “Divine Vehemence”, namely, ritual, amatorial, prophetic and creative, are subjected to the analysis. The research reveals that the Poetic Vehemence is intrinsically syncretical and ambivalent. It inherits both Apollo’s prophetic gift and Dionysus’s chthonian power as well as Eros’s metamorphoses and Muses’ wisdom. It seems quite possible that the above attributes predetermined the development of the belief in art uniqueness first in the Greek Myth and later in the European mentality. Sadovskaya Irina Gennadievna - candidate of linguistics, professor assistant